The Influence of Ethnicity on the Development of Type 2 Diabetes Mellitus in Women with Gestational Diabetes: A Prospective Study and Review of the Literature. (17th April 2012) - Girgis, Christian M.; Gunton, Jenny E.; Cheung, N. Wah
Abstract : As the worldwide prevalence of type 2 diabetes continues to rise at an alarming rate, the search for susceptible populations likely to benefit from preventative measures becomes more important. One such population is women with a previous history of gestational diabetes mellitus (GDM). In this prospective study of 101 women who had GDM in Australia, ethnicity was a major risk factor for the development of diabetes following a diagnosis of GDM. With a mean followup of 5.5 years after GDM, South Asian women had a significantly higher risk of developing abnormal glucose tolerance (AGT) (69%) than women of all other ethnicities (P < 0.05 ). The prevalence of diabetes and impaired glucose tolerance was also very high amongst other groups: South East and East Asian (11/27, 41%), Middle-Eastern (8/18, 44%), South European backgrounds (5/12, 42%), and Australian-born women 39% (11/28). A review of the literature supports the role of ethnicity in the development of diabetes amongst these women. These findings have implications for South Asian countries and countries such as Australia where there is a population from diverse ethnic backgrounds and where the implementation of targeted measures to stem the growing tide of diabetes is needed.